AKIBAT PEMBERIAN PUPUK MAGNESIUM SULFAT DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Mico Saputra, Whin Themas; Hairunnas, Hairunnas; Sahri, Sahri (Cangkok, 2024)
Chili pepper (Capsicum frutescens L.) is one of the horticultural plant commodities that is in great demand and is classified as an important vegetable commodity because it has a high economic value among the Indonesian people. Fertilization is an effort made with the aim of replacing lost nutrients and increasing the supply of nutrients needed by plants to increase plant production and quality. This study used a Randomized Block Design (RAK) factorial pattern consisting of 3 treatment levels. The first factor is magnesium sulfate fertilizer, consisting of 3 (three) levels, namely: M1 = 36 grams / plot (4 grams / plant), M2 = 54 grams / plot (6 grams / plant), M3 = 72 grams / plot (8 grams / plant). The second factor is the dose of Mutiara NPK fertilizer consisting of 3 levels, namely: N1 = 50 grams / plot (5.5 grams / plant), N2 = 75 grams / plot (8.3 grams / plant), N3 = 100 grams / plot (11 grams / plant). Research results The treatment of magnesium sulfate and NPK fertilizer doses had a very significant effect on plant height, number of leaves at 20, 30 and 40 days after planting, and fruit weight per plant and per plot at 90 and 120 days after planting. The administration of a dose of 72 grams/plot (M3) and a dose of NPK 100 grams/plot (N3) showed the best results for plant growth and yield parameters. There was also a significant interaction with fruit weight per plant at 90 days after planting